Preparation of Magnetic Base map Information (Total Magnetic Field) for Iraq in scale 1:1000000 using GIS system for strategic and industrial site selection projects studies. - Muhana Mit3b Ahmed (Tikrit Journal of Pure Science)
The preparation of total magnetic field anomaly map scale 1:1000000 , has been based on the magnetic field map of the same scale, prepared by French company C.G.G. in 1974 [1]. This map has offered with a contour interval 20 gamma on a base map of scale 1: 1000000, which also contained the basic topographic features of rivers, lakes  and main valleys, in addition to the cities and the main illustration sites .